Synthesis of O6-alkylated preQ1 derivatives - Flemmich, Laurin; Moreno, Sarah; Micura, Ronald (Beilstein Journal of Organic Chemistry, 2021)
A naturally occurring riboswitch can utilize 7-aminomethyl-O6-methyl-7-deazaguanine (m6preQ1) as cofactor for methyl group transfer resulting in cytosine methylation. This recently discovered riboswitch-ribozyme activity opens new avenues for the development of RNA labeling tools based on tailored O6-alkylated preQ1 derivatives. Here, we report a robust synthesis for this class of pyrrolo[2,3-d]pyrimidines starting from readily accessible N2-pivaloyl-protected 6-chloro-7-cyano-7-deazaguanine. Substitution of the 6-chloro atom with the alcoholate of interest proceeds straightforward. The transformation of the 7-cyano substituent into the required aminomethyl group turned out to be challenging and was solved by a hydration reaction sequence on a well-soluble dimethoxytritylated precursor via in situ oxime formation. The synthetic path now provides a solid foundation to access O6-alkylated 7-aminomethyl-7-deazaguanines for the development of RNA labeling tools based on the preQ1 class-I riboswitch scaffold.
Keywords: deazapurines; heterocycles; pyrrolopyrimidines; queuosine; RNA cofactors; RNA methylation